(untitled) (De Legibus - Law Journal, 2021)
Tax evasion and the need for more revenue in the Social State pose the problem of balancing the power to tax and the duty to contribute. The Tax Administration needs a margin of freedom in the assessment and investigation of tax situations. On the other hand, the taxpayer needs to see compensated for the increase in discretion with more guarantees, through the contradictory in the tax procedure and, above all, through effective and full judicial control of tax acts. It is essential to ensure that discretion does not result in arbitrariness, and to prevent the tax function from developing outside the law.